Improving Surgical Access in Rural Africa through a Surgical Camp Model. (16th June 2016) - Galukande, M.; Kituuka, O.; Elobu, E.; Jombwe, J.; Sekabira, J.; Butler, Elissa; Faulal, J.
Abstract : Introduction . Surgical camps are preplanned activities where volunteer surgical teams congregate at specified place(s) and perform a wide range of mostly elective procedures for a limited period of time. This is usually at no cost to the patients, who belong to vulnerable (poor and hard to reach) communities. We describe a surgical camp model and its challenges as a means of improving access to surgical services. Methods . A cross-sectional descriptive study. Data from a recent Association of Surgeons of Uganda surgical camp were collected and analyzed for demographics, costs, procedure types, and rates and, in addition, challenges encountered and solutions. Personnel that participated in this exercise included specialist surgeons, surgical residents, medical officers, clinical officers, anesthetists, and theater nurses (a total of 121 staff). Results . In total, 551 procedures were performed during a four-day-long camp. Mean age was 35 years (SD 23), M : F ratio was 2 : 1. Herniorrhaphy, skin lump excision, hydrocelectomy, and thyroidectomy formed 81% of all the procedures. Average cost per procedure was 73 USD. Conclusion . Surgical camps offer increased access to surgical services to vulnerable populations. Hernias and goiters were most common. Surgical camps should become an integral part of the Health Service delivery in low-resourced environments.